1991
DOI: 10.1111/j.1365-2362.1991.tb01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased removal of remnants of triglyceride‐rich lipoproteins on a diet rich in polyunsaturated fatty acids

Abstract: We studied the effect of two diets, one rich in polyunsaturated and the other in saturated fatty acids, on the postprandial processing of exogenous and endogenous triglyceride-rich lipoproteins (chylomicrons, very-low-density lipoproteins, and their remnants). For this purpose, 12 normolipidaemic young volunteers were fed, in a cross-over design of 9 days on each diet, either a diet rich in saturated fat (21% of their daily energy intake from saturated fat, 12% from monounsaturated fat, and 3% from polyunsatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
33
0
3

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 42 publications
7
33
0
3
Order By: Relevance
“…Similarly, and consistent with findings of animal studies in which LDL clearance was increased with PUFA feeding^o.u,13.3536 increased body elimination of sterol would be expected to result in more rapid clearance of lipoprotein cholesterol, as has been observed in humans consuming PUFA diets. 41 The present results are consistent with the concept that in humans, feeding corn oil causes enhanced cholesterogenesis, either in response to increased whole-body excretion and plasma removal of cholesterol or as a consequence of oil fatty acid profile or content of some nonsaponifiable component.…”
supporting
confidence: 91%
“…Similarly, and consistent with findings of animal studies in which LDL clearance was increased with PUFA feeding^o.u,13.3536 increased body elimination of sterol would be expected to result in more rapid clearance of lipoprotein cholesterol, as has been observed in humans consuming PUFA diets. 41 The present results are consistent with the concept that in humans, feeding corn oil causes enhanced cholesterogenesis, either in response to increased whole-body excretion and plasma removal of cholesterol or as a consequence of oil fatty acid profile or content of some nonsaponifiable component.…”
supporting
confidence: 91%
“…Thus, their study cannot be compared with ours, in which saturated fat was held constant, and monounsaturated and polyunsaturated fat levels were altered modestly. Similarly, the study by Demacker et al, 45 in which lower 24-hour lipid and lipoprotein levels were observed during consumption of a high-polyunsaturated fat diet, differs from ours in both saturated and polyunsaturated fatty acid content. Thus, in contrast to other data in the literature confounded by reciprocal changes in saturated and polyunsaturated fats, our data suggested that neither polyunsaturated nor monounsaturated fatty acids affect the metabolism of postprandial lipoproteins when saturated fat and carbohydrates are held constant.…”
supporting
confidence: 65%
“…In some instances, investigators have chosen to measure response to a test meal which has the same fatty acid composition as the background diet being fed. This is the case with the study of Demacker et al (1991) who altered the diets of free-living subjects so that either butterfat or safflower oil was the predominant fat used in cooking and in meals prepared at their work place. After 3 weeks on each diet, subjects responses to a breakfast, lunch and dinner were monitored over a 24 h period.…”
Section: Effects Of Background Dietary Fa'ity Acid Intake On Postpranmentioning
confidence: 99%